Evaluation of Law Enforcement on Consumer Protection in Online Sales and Purchase Agreements - Frederik, Wulanmas APG; Ringkuangan, Deine; Tuwaidan, Herry (International Journal of Law, Environment, and Natural Resources, 2025)
Online buying and selling activities are now increasingly widespread, especially as the sites used for conducting online buying and selling transactions are becoming better and more diverse. However, in the online buying and selling system, the products offered are only in the form of explanations of product specifications and images, the truth of which cannot be guaranteed. For this reason, Consumer Independence is needed in conducting Online Buying and Selling Transactions as an effort to protect themselves as mandated by Law Number 8 of 1999 concerning Consumer Protection. The objectives of this research are to examine and analyze: 1). Legal Protection for consumers in Online Buying and Selling Transactions; 2). Evaluation of the Effectiveness of Consumer Protection Law Enforcement in Online Sales and Purchase Agreements. This research goes through 3 stages, namely: 1). The initial stage, consisting of the initial meeting of the Research Team and the division of tasks; 2). The Implementation Stage, namely: Data collection, Monitoring, Discussion of the results of data collection; 3). The Final Stage, namely: Preparation of Research Results. As for the literature, empirical data collection was also carried out using tools. The research approach method used in this study is the Empirical Juridical approach. Data collection techniques, in addition to using a Juridical approach, were obtained through research in the form of interviews. Furthermore, data analysis in this study was carried out qualitatively. The results of this research describe the Evaluation of Law Enforcement in Online Buying and Selling Transactions.